Old-Age Government Transfers and the Crowding Out of Private Gifts: The 70 and Above Program for the Rural Elderly in Mexico - Catalina Amuedo-Dorantes; Laura Juarez (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
We estimate the crowding out of private transfers caused by 70 y Más -a public assistance program for the rural elderly in Mexico for whom family support is an important source of income. Using data from the Mexican Income and Expenditure Survey and a triple difference approach, we find that the program crowds out private gifts by 37 percent, and it does so mostly by reducing the probability of receiving domestic remittances. As a result, the non-labor income of beneficiaries increases by less than their government transfers. Thus, by reducing their private support to the elderly, domestic donors are dampening the effect of the program, although not completely neutralizing it.
Keywords: H3; H55; J14; J18; 330